EDUCATIONAL ACTIVITY AS THE GROWTH FACTOR OF PROFESSIONAL ACTIVITY OF ELDERLY PEOPLE - Niewiadomska, Anna; Sobolewska-Poniedziałek, Ewa (Acta Scientiarum Polonorum. Oeconomia, 2016)
The article undertakes the problem of the educational activity of elderly people. The research objective is, on the one side, showing the correlation between professional activity of elderly Polish people and their level of education, and on the other hand, the presentation of own research illustrating the attitude and experience of elderly people in the area of education and professional training. The analysis is made based on own research as well as the secondary data which picture educational and professional activity of elderly Poles against the background of the European Union member states. Comparative analysis of the level of educational involvement, measured by means of participation in education and professional training shown elderly Polish people take part in the process of improving qualification in a smaller degree than the inhabitant of the EU. At the same time regularity, manifesting itself in an increase in the level of their professional engagement proportionally to higher levels of education, can be observed. The results of own study showed that the majority of respondents recognize the important role of educational activity in the context of an individual's position in the labor market. As many as 65% of respondents believed that education, both formal and informal learning, is crucial for maintaining employment or finding job. At the same time more than 74.6% have not been learning in the last 10 years.